Producing organic fertilizer from restaurant food waste using composting method - Ahmad Fauzan Wahab (2020)
Restaurant produced food wastes every day and this caused a problem in waste management system. It used up a large amount of land, water and fertilizer only to be buried in a landfill. The food in landfill decomposes and emits methane gas which contribute to global warming. Three proportion of mixture was made such as 100% soil, 75% soil + 25% compost, 100 % compost. Next, the physicochemical properties were analysed in the compost which are colour, texture, odour, humidity and bulk of density. To compare the physicochemical content in 100% soil, 75% soil + 25% compost, 100 % compost using one-way ANOVA analysis. The food waste was collected from the restaurant area Jeli, Kelantan and the location to carry the process of composting is located at Tanah Merah, Kelantan. The physical characteristic for compost-like smell and dark brown in colour which means it is matured enough to be used. For the humidity of compost was 66% and bulk density of compost was 0.55 g/cm3. Moreover, the physicochemical content was compared in 100% soil, 75% soil + 25% compost, 100 % compost. The pH value for 100% soil, 75% soil + 25% compost, 100 % compost are 7.30, 7.38, 7.34. In this study, the Nitrogen content for soil, soil + compost, and compost is 0.11%, 0.21% and 2.44%. Phosphorus is the other primary nutrients for plant. Lastly, after conducting the composting, the value of potassium for compost, soil + compost and soil are 33.03, 4.28 and 0.88. Keywords: one-way ANOVA analysis, bulk of density and humidity. FYP